(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
terrorism, focusing especially on the experiences of those who went through the kidnapping and disappearance of their relatives without finding a place of belonging in the struggle of human rights organizations or in the humanitarian discourse. These testimonies show the distance that exists between the public discourse on reparation and what can happen in the private and subjective sphere in terms of the vulnerability of the witnesses and the helplessness they express in their stories. The work is based on interviews from the Oral Archive of Memoria Abierta.